Urological anomalies associated with obstructed hemivagina and ipsilateral renal anomaly (OHVIRA) syndrome, a case series - Yasuo Nakahara; Soichi Nakada; Kosuke Hitomi; Shojiro Hanaki; Keisuke Doi; Takafumi Goto; Koji Aoyama (Elsevier, 2020)
We report four patients with obstructed hemivagina and ipsilateral renal anomaly (OHVIRA) syndrome associated with a urological anomaly other than typical renal agenesis. Three patients had a dysplastic kidney and an ectopic ureter to the vagina, and one had a vesicovaginal fistula. Although the timing of surgery differed, all patients underwent vaginal septum resection. The vesicovaginal fistula was repaired laparoscopically, and the patient was asymptomatic one year later. In the remaining three patients, resection of the dysplastic kidney and ureteral ligation were both effective procedures for the management of urine drainage from the vagina. These anomalies originate from abnormal development of the Wolffian and Mullerian ducts. Knowledge of these variants is essential for effective preoperative investigation and surgical planning. Keywords: OHVIRA syndrome, Uterine anomaly, Urogenital abnormalities, Vesicovaginal fistula, Ectopic ureter